Impact of target cost technologyin determining the dimensions of internal control (Applied studyin the State Company for Soft Drinks Manufacturing) - Meatab, Haider Layth; Hasan, Majid Gazi; Mutasher, HawraaN. (International Journal of Psychosocial Rehabilitation, 2020)
The research dealt with the role of target costs in achieving accurate control over cost elements, considered the modern approaches reduce costs by fully activating the role of internal control, identify weaknesses that increase the cost of production, increase market competitiveness and continuity,the research problem was to identify deficiencies in the traditional method used in the company, the sample of the research, led to a weakness in cost control, the researcher relied on the company’s data and costs,the research recommended the need to apply the target cost and activate internal control, give a role in monitoring the production costs in the company, the research sample, training the workers, and preparing training courses for them, stressed the need to address the obstacles that prevent an effective cost system, including the application of the target cost method in the research sample company.